Pengaruh Bimbingan Kelompok dan Teknik Role Playing terhadap Pengentasan Gangguan Kecemasan Sosial Peserta Didik - Gulo, Mirsiarni; Lase, Famahato; Lase, Justin Foera-era; Damanik, Hosianna Rodearni (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study examined the effectiveness of group guidance services employing role-playing techniques in reducing social anxiety among eighth-grade students. A quantitative approach was applied using a quasi-experimental one-group pretest–posttest design. The population consisted of 60 students, and 30 participants were selected through purposive sampling based on initial screening results indicating moderate to high levels of social anxiety. Data were collected using a Likert-scale social anxiety questionnaire developed from established theoretical indicators and tested for validity and reliability through a pilot study. Data collection was conducted in two stages: pretest administration prior to the intervention and posttest following four structured treatment sessions. Data analysis began with prerequisite tests, including normality (Shapiro–Wilk), homogeneity (Levene’s test), and linearity, confirming that the data met parametric assumptions. Hypothesis testing was conducted using a paired sample t-test, followed by multiple regression analysis to examine simultaneous effects, and the coefficient of determination (R²) to measure effect size. The findings revealed a statistically significant decrease in social anxiety scores after the intervention, with an effective contribution of 66.8%, indicating both statistical and substantive impact of the treatment.